Adiponectin and Testosterone Levels and Their Correlations with Fertility in Anglo-Nubian x Etawah Grade Crossbred Bucks - Hafizuddin Hafizuddin; N. W. K. Karja; L. Praharani; M. A. Setiadi (Tropical Animal Science Journal, 2020)
The purpose of the current study was to determine the concentrations of adiponectin and testosterone in various ages of bucks as well as the correlations of adiponectin and testosterone with semen quality as an indicator of fertility. Nineteen Anglo Nubian (AN) x Etawah Grade (PE) (Anpera) crossbred bucks belonged to the Research Institute for Animal Production were classified into four different age groups: 24 months, 30 months, 36 months, and more than 48 months. The concentrations of adiponectin and testosterone in the samples of blood plasma were analyzed using enzyme-linked immunosorbent assay (ELISA). The semen characteristics were evaluated both macroscopically and microscopically. The results of the study showed that plasma concentrations of adiponectin in Anpera bucks at the ages of 24, 30, 36, and more than 48 months were 14.10±1.73 mg/L, 18.36±8.25 mg/L, 20.38±8.67 mg/L, and 15.41±7.31 mg/L, respectively. There was no significant difference in adiponectin concentrations among the age groups (p>0.05). However, there were correlations of adiponectin concentrations with semen volume, sperm morphology, and sperm concentration. Plasma concentrations of testosterone at the ages of 24, 30, 36, and more than 48 months were 9.76±2.46 ng/mL, 9.81±1.56 ng/mL, 10.05±0.94 ng/mL, and 9.93±2.71 ng/mL, respectively. Plasma concentrations of testosterone in Anpera bucks also did not demonstrate a significant difference among the age groups (p>0.05). However, plasma testosterone concentrations had significant correlations with semen volume, sperm motility, and sperm concentration. In conclusion, the plasma concentrations of adiponectin and testosterone hormones had correlations with the semen quality parameters, which are related to fertility.